2008
DOI: 10.3378/1534-6617-80.6.611
|View full text |Cite
|
Sign up to set email alerts
|

Twinning and Its Correlates: Community-Based Study in a Rural Area of India

Abstract: A retrospective study was carried out to investigate the twinning rate and its correlates from January 1991 to December 2005 in 10 villages of the Rural Health Centre, Pohir, a field practice area of the Department of Community Medicine, Dayanand Medical College and Hospital, Ludhiana, Punjab, India. During this study period, 5070 deliveries took place. A total of 5017 singleton births and 53 sets of twins were recorded, giving a twinning rate of 10.45 per 1000 total deliveries. Monozygotic and dizygotic twinn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…[9][10][11]14 Literature supports the fact that complications are fewer in dichorionic than monochorionic twins. Dichorionicity being the majority contributes to the study having less fetal complications and better perinatal outcome.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…[9][10][11]14 Literature supports the fact that complications are fewer in dichorionic than monochorionic twins. Dichorionicity being the majority contributes to the study having less fetal complications and better perinatal outcome.…”
mentioning
confidence: 61%
“…16 A history of twins in the family was there in 40.4 % of patients in the present study. Yet only 10% association with family history was found in a study done by Satija et al 11 The inadvertent use of ovulation induction drugs and ART has contributed to the rise in higher order of gestation. Ovulation induction was done in 32% of patients in our study, out of which 3 were In-vitro fertilization pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Perinatal mortality was found to be higher among the group in which diagnosis of twin was not done during antenatal period indicating need for special preparation for conducting twin deliveries 12 .…”
Section: Resultsmentioning
confidence: 98%
“…It is said that twinning rate in hospital based studies may be higher than would be observed in the population since twins would be more likely to deliver at hospitals 5 . Twin rate in rural community of India and Thailand was reported to be 9.01 and 8.6 per 1000 delivery respectively 12,13 . In Denmark between 1980-94 the twinning rate was reported to be 12.1 per 1000 pregnancies and there was history of use of ovulation induction and advanced reproduction technique in about a quarter of multiple births 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation